Pembangunan Screenhouse Sebagai Upaya Peningkatan Produktivitas Tanaman Di Dusun Ngadilegi Utara, Kecamatan Pandaan, Kabupaten Pasuruan - Ari Wibisono; Muhammad Farhan Firmansyah; Purnomo Edi Sasongko (Jurnal Nusantara Berbakti, 2024)
Ngadilegi Utara Hamlet is one of the hamlets of Plintahan Village, Pandaan District, which has great potential in the agricultural sector. However, global climate change has caused problems that Ngadilegi Utara farmers, especially the Madulegi Farmer Group, must face in cultivating crops. The impact of global climate change can trigger the emergence of plant pest organisms (OPT) which can affect the achievement of quality to meet market demand (consumers). Meanwhile, farmers in Ngadilegi Utara Hamlet still carry out crop cultivation activities on open land which is very potential for pest and disease attacks, and can be disrupted by environmental stress. Cultivation innovation using a screenhouse is one solution to overcome the problem in order to increase plant productivity. The screenhouse was built with a size of 6 x 8 meters using a hollow and galvanized C frame. The roof uses UV plastic with a thickness of 200 microns, the walls use insect net with a density of 50 mesh, and the base is covered using tarpaulin. The construction of the screenhouse in Ngadilegi Utara Hamlet is considered to reduce the attack of plant pest organisms (OPT) and environmental stress factors, so that farmer groups in Ngadilegi Utara Hamlet can increase crop productivity well.